Protective effects of black bamboo leaves on the glucose-induced toxicity in Caenorhabditis elegans - Eun Hye Park; Hong Jun Kim; Dong Seok Cha (Shahrekord University of Medical Sciences, 2021)
Introduction: Previous studies have suggested that high glucose (HG) condition shortens the lifespan of worms by increasing glycolytic flux followed by accelerating reactive oxygen species (ROS) production, termed glucose toxicity. This study was designed to investigate the protective effects of the leaves of black bamboo (Phyllostachys nigra var. henosis) on the HG-induced toxicity using Caenorhabditis elegans model system. Methods: To determine the effect of black bamboo leaf extract (BLE) against HG-induced toxicity, lifespan assay was carried out with wild-type and daf-16 null mutant worms under 2% glucose condition. The involvement of DAF-16 was further confirmed by observing fluorescence signal of transgenic mutant carrying DAF-16::GFP transgene. ROS levels and glucose concentration of worms were analyzed using fluorescent probe H2DCF-DA and glucose meter, respectively. Nile-red staining was carried out to evaluate the lipid storage of worms. Intercellular lipid accumulation was measured using Oil-Red O staining method. Results: BLE strongly extended the lifespan of worms under not only normal culture condition but also HG condition. Our additional studies suggested that DAF-16 activation was responsible for BLE-mediated longevity and protective action against glucose toxicity. In addition, HG-fed worms showed increased ROS generation, and it was completely normalized by BLE treatment. Moreover, BLE reduced body glucose concentration and lipid accumulation in HG-fed worms. We further confirmed the inhibitory effect of BLE on lipid storage under HG condition using 3T3-L1 adipocytes. Conclusion: These therapeutic values of BLE on glucose toxicity raise the possibility that BLE might have beneficial effects on the pathogenesis of diabetes mellitus.